2006
DOI: 10.1194/jlr.m600312-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Heritability and genetic loci of fatty liver in familial combined hyperlipidemia

Abstract: VLDL overproduction, a process that is driven by an excess amount of hepatic fat, is a well-documented feature of familial combined hyperlipidemia (FCHL). The aims of this study were to investigate whether fatty liver, measured with ultrasound and as plasma alanine aminotransferase (ALT) levels, develops against a genetic background in FCHL and to identify chromosomal loci that are linked to these traits. In total, 157 FCHL family members and 20 spouses participated in this study. Radiological evidence of fatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 43 publications
2
62
0
1
Order By: Relevance
“…LDL-cholesterol was calculated using the Friedewald formula [13]. NEFA were assessed in EDTA plasma using an enzymatic colorimetric method (NEFA-C; Wako Chemicals, Neuss, Germany) [14]. Blood pressure was measured using an oscillometric precision blood pressure instrument (Maxi-Stabol 3; Speidel & Keller, now Welch Allyn, Skaneateles Falls, NY, USA) [15].…”
Section: Methodsmentioning
confidence: 99%
“…LDL-cholesterol was calculated using the Friedewald formula [13]. NEFA were assessed in EDTA plasma using an enzymatic colorimetric method (NEFA-C; Wako Chemicals, Neuss, Germany) [14]. Blood pressure was measured using an oscillometric precision blood pressure instrument (Maxi-Stabol 3; Speidel & Keller, now Welch Allyn, Skaneateles Falls, NY, USA) [15].…”
Section: Methodsmentioning
confidence: 99%
“…A family study of 157 individuals with familial combined hyperlipidemia showed that both the presence of fatty liver and the levels of alanine aminotransferase (ALT) were increased both in index dyslipidemic patients and in normolipidemic family members. 59 A case-control family aggregation study of 20 NAFLD patients showed that IR occurs more commonly within families of NAFLD patients, with significantly higher risks of T2DM…”
Section: Family Studiesmentioning
confidence: 99%
“…Brouwers et al used nonparametric quantitative trait locus analysis to identify three loci associated with fatty liver in males, as determined by serum alanine aminotransferase (ALT) activity and ultrasound in 157 members from Dutch familial combined hyperlipidemia kindred ( 48 ). Of the familial combined hyperlipidemia probands, 40% had fatty liver, compared with 35% of relatives and 15% of spouses.…”
Section: Impaired Hepatic Triglyceride Exportmentioning
confidence: 99%